Haemangioma of the Small Intestine: A Rare Case Report (Jalalabad Medical Journal, 2025)
Small bowel haemangiomas are rare benign vascular tumour that arises from fast-growing embryonic mesodermal tissue and are characterized by the proliferation of endothelial cells which manifests themselves in different forms, locations and dimensions. We report a case of a haemangioma located in the distal part of the ileum of an 18 years old female with a history of occasional abdominal pain and vomiting. An imaging study showed large segmental thickening of the wall and luminal narrowing at the distal ileum with proximal dilatation and a small haemangioma on the right lobe of the liver. Surgery was performed and histopathology confirmed the diagnosis.Jalalabad Med J 2024; 21 (1): 26-28